2013
DOI: 10.1085/jgp.201210948
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-dependent processes in the electroneutral amino acid exchanger ASCT2

Abstract: Neutral amino acid exchange by the alanine serine cysteine transporter (ASCT)2 was reported to be electroneutral and coupled to the cotransport of one Na+ ion. The cotransported sodium ion carries positive charge. Therefore, it is possible that amino acid exchange is voltage dependent. However, little information is available on the electrical properties of the ASCT2 amino acid transport process. Here, we have used a combination of experimental and computational approaches to determine the details of the amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 49 publications
(107 reference statements)
7
53
0
Order By: Relevance
“…More recently, Zander et al (24) demonstrated that Na ϩ dependence of ASCT2 anion currents is biphasic, suggesting that ASCT2 is coupled to at least two Na ϩ ions. MD simulations in this study similarly suggest the presence of at least two, and possibly three, Na ϩ binding sites in ASCT2 (24). To probe Na ϩ binding sites in ASCTs we mutated coordinating residues within each of the sites proposed for the EAATs and Glt Ph .…”
supporting
confidence: 57%
See 1 more Smart Citation
“…More recently, Zander et al (24) demonstrated that Na ϩ dependence of ASCT2 anion currents is biphasic, suggesting that ASCT2 is coupled to at least two Na ϩ ions. MD simulations in this study similarly suggest the presence of at least two, and possibly three, Na ϩ binding sites in ASCT2 (24). To probe Na ϩ binding sites in ASCTs we mutated coordinating residues within each of the sites proposed for the EAATs and Glt Ph .…”
supporting
confidence: 57%
“…Previous studies have reported a much higher Na ϩ affinity for ASCT2 in the absence of substrate (0.25-2.0 mM) (23,24) compared with the EAATs (EAAT3 is 100 mM (17)). This raises the question: is Na ϩ unbinding during ASCT-mediated exchange, or does Na ϩ function as an allosteric modulator at some of the Na ϩ sites?…”
Section: Asct1-d380n/d467smentioning
confidence: 87%
“…ASCT2 belongs to the solute carrier 1 (SLC1) family of transporters [3]. It transports neutral amino acids, including glutamine, across the plasma membrane in exchange with an intracellular neutral amino acid [45]. The process is dependent on Na + , but not driven by the transmembrane concentration gradient of Na + .…”
mentioning
confidence: 99%
“…This may be valid also for ASCT2, whose rat an human (Fig. 1) homology models have been constructed using the Gltph as template (Albers et al, 2012;Oppedisano et al, 2010;Pingitore et al, 2013;Zander et al, 2013). Significant differences between the rat and humanisoforms, in a region predicted in the vicinity of the substrate binding site were found (Oppedisano et al, 2010).…”
Section: Slc1a5: Asct2mentioning
confidence: 82%
“…The overall transport reaction of hASCT2 follows a random simultaneous mechanism as recently reported in proteoliposomes . A functional aspect still underneath is the electrical nature of the transport reaction; after several contradictory reports (Utsunomiya-Tate et al, 1996;Zander et al, 2013), this issue has been recently dealt with the purified hASCT2, demonstrating a positive regulation by imposed membrane potential due to an electrogenic component in the substrates translocation . Under a physiological point of view, hASCT2 is involved in amino acid absorption in epithelia and other tissues contributing to the glutamine-glutamate cycle in brain and placenta.…”
Section: Slc1a5: Asct2mentioning
confidence: 99%